Possibility of Industrial Application of Clostridium papyrosolvens’ New Strain by Purification and Kinetic Studies of Exo-\(β\)-1, 4- glucanase and Endo- \(β\)-1,4-glucanase - Tirumale, Sharmila; Soumya, K.; Sreelatha, G. L.; Krishnanand (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
Cellulose is the largest waste component, thus creating a serious pollution problem. Anaerobic bacteria producing cellulases have not been extensively studied though they are the efficient producers of cellulase. The anaerobic cellulolytic bacterium, Clostridium papyrosolvens was isolated from a consortium developed in the laboratory from the compost sample collected in the surroundings of Mysore, Karnataka, India. Clostridium papyrosolvens CFR-1010, an anaerobic cellulolytic bacterial strain was identified as a potent cellulase producer and selected for the purification and kinetic studies of Exo-\(β\)-1,4-glucanase and Endo-\(β\)-1,4- glucanase. The molecular masses of the enzymes were 65 and 60 kDa, respectively. The enzymes showed maximum activities at pH 5.0 and at a temperature of 50oC. The activities increased in the presence of MnCl2, whereas, N-bromosuccinimide decreased enzyme activities by 68 and 75% respectively, thus suggesting the presence of tryptophan residues at the active sites of enzymes. Exoglucanase had a Km of 20 mg/ml and Vmax of 22 units/min/mg of protein whereas the endoglucanase exhibited a Km of 6.66mg/ml and Vmax of 11.76 units/min/mg of protein. Results of the present studies suggest the use of C. papyrosolvens for cellulase production in shorter periods of time and they also add significance for the exploration of this organism for industrial applications. The exo \(β\)-1,4-glucanse and endo-\(β\)-1,4-glucanase from C. papyrosolvens CFR-1010 are applicable for the biodegradation of cellulosic wastes which can be used in the biogas digesters and for the commercial production of glucose or various other fermentation products.